Self-supported PdNi dendrite on Ni foam for improving monohydric alcohol and polyhydric alcohols electrooxidation. (15th October 2022) - Zhang, Ning; Wang, Jing; Zhang, Wen; Zhao, Yingxiu; Dong, Zemeng; Wu, Zexing; Xu, Guang-Rui; Wang, Lei
Graphical abstract: Highlights: The self-supported PdNi dendrites on Ni Form (self-supported PdNi DNTs/NF) were synthesized by a simple self-sacrificing template and hydrothermal methods. The morphological structure of self-supported PdNi DNTs/NF is similar to the stem-and-leaf of fir, which possesses a stems erect and leaves lanceolate or lanceolate. The mass activity and specific activity of self-supported PdNi DNTs/NF for glycerol oxidation are 2451.6 mA mgcat -1 and 10.84 mA cm −2, respectively, as well as ethanol oxidation (2375.7 mgcat -1 and 10.07 mA cm −2 ), which should attribute to abundant active sites and high-index facets/low-coordinated atoms on the edge. The PdNi DNTs/NF exhibit outstanding long-term durability in the current–time test for 7200 s with superior anti-CO poisoning performance due to the 3D self-supported structure. Abstract: Despite considerable efforts to study direct alcohol fuel cells (DAFCs), the development of efficient bifunctional catalysts for monohydric alcohol and polyhydric alcohols remains a great challenge. This work reports the preparation of self-supported PdNi dendrites on Ni foam (self-supported PdNi DNTs/NF) with a large specific surface area by a simple self-sacrificing template and hydrothermal method. The presence of NF with enrichment of nucleation sites is crucial for the generation of self-supported PdNi DNTs. The as-obtained self-supported PdNi DNTs/NF exhibits an excellent property for ethanol and glycerol electrooxidation with the mass activity of 2375.7 mA mgcat −1 and 2451.6 mA mgcat −1, the specific activity of 10.07 mA cm −2 and 10.84 mA cm −2, respectively, in alkaline media, which should attribute to abundant high-index facets and low-coordinated atoms on the edge of branches. Furthermore, the PdNi DNTs/NF exhibits outstanding long-term durability in the current–time test for 7200 s with superior anti-CO poisoning performance, possessing a potential application in DAFCs.